Evaluasi Kinerja Waktu dan Biaya Proyek Melalui Pengaplikasian Metode Earned Value: Studi Kasus Pada Pembangunan Ruas Jalan Sp. Armed Rumah-Great Kec. Biru-Biru Kab. Deli Serdang - Sederhana Laia; Sheila Hani; Rini Rini (Majalah Ilmiah METHODA, 2024)
Project delays are caused by lack of good control, which affects the time and cost of completion, in determining and knowing the time performance and cost performance of the SP. Armed-Rumah Great Road Construction Project, Biru-Biru District, Deli Serdang Regency. Using the Earned Value method. Based on the results, the results of the time performance from month 1 to month 3 of the project experienced delays, this is indicated by the Schedule Variant (SV) indicator which has a negative value of Rp. - 356,103,446.04 or Schedule Performance Index (SPI) = 0.828 <1. In the 4th month it was faster than the planned schedule, this is indicated by the Schedule Variant (SV) indicator which has a positive value of Rp. 96,183,088.74 or Schedule Performance Index (SPI) = 1.019>1. And in the 5th and 6th months the schedule performance index (SPI) value shows a value of 1 which means that the construction project work is in accordance. Meanwhile, for cost performance from month 1 to month 3, it incurred smaller costs than planned, this is indicated by the negative Cost Variance (CV) indicator of Rp. -150,413,906.18 or Cost Performance Index (CPI) = 0.920 <1. In month 4 to month 6, the Cost Variance CV value is above the X axis with a positive value of Rp. 829,560,555.98 or Cost Performance Index (CPI) = 1.110 >1 due to the addition of labor and additional working hours in project implementation.